Impairment of Base Excision Repair in Dermal Fibroblasts Isolated From Nevoid Basal Cell Carcinoma Patients - Charazac, Aurélie; Fayyad, Nour; Beal, David; Bourgoin-Voillard, Sandrine; Seve, Michel; Sauvaigo, Sylvie; Lamartine, Jérôme; Soularue, Pascal; Moratille, Sandra; Martin, Michèle T.; Ravanat, Jean-Luc; Douki, Thierry; et al. (Frontiers in Oncology, 2020)
The nevoid basal cell carcinoma syndrome (NBCCS), also called Gorlin syndrome is an autosomal dominant disorder whose incidence is estimated at about 1 per 55 600 - 256 000 individuals. It is characterized by several developmental abnormalities and an increased predisposition to the development of basal cell carcinomas (BCCs). Cutaneous fibroblasts from Gorlin patients have been shown to exhibit an increased sensitivity to ionizing radiations. Mutations in the tumor suppressor gene PTCH1, which is part of the Sonic Hedgehog (SHH) signaling pathway, are responsible for these clinical manifestations. As several genetic mutations in the DNA repair genes are responsible of photo or radiosensitivity and high predisposition to cancers, we hypothesized that these effects in Gorlin syndrome might be due to a defect in the DNA damage response (DDR) and/or the DNA repair capacities. Therefore, the objective of this work was to investigate the sensitivity of skin fibroblasts from NBCCS patients to different DNA damaging agents and to determine the ability of these agents to modulate the DNA repair capacities. Gorlin fibroblasts showed high radiosensitivity and also less resistance to oxidative stress-inducing agents when compared to control fibroblast obtained from healthy individuals. Gorlin fibroblasts harboring PTCH1 mutations were more sensitive to the exposure to ionizing radiation and to UVA. However, no difference in cell viability was shown after exposure to UVB or bleomycin. As BER is responsible for the repair of oxidative DNA damage, we decided to assess the BER pathway efficacy in Gorlin fibroblasts. Interestingly, a concomitant decrease of both BER gene expression and BER protein activity was observed in Gorlin fibroblasts when compared to control. Our results suggest that low levels of DNA repair within Gorlin cells would lead to an accumulation of oxidative DNA damage that could participate and partly explain the radiosensitivity and the BCC-prone phenotype in Gorlin syndrome.